Astrocyte HIV-1 Tat Differentially Modulates Behavior and Brain MMP/TIMP Balance During Short and Prolonged Induction in Transgenic Mice - Joshi, Chaitanya R.; Stacy, Satomi; Sumien, Nathalie; Ghorpade, Anuja; Borgmann, Kathleen (Frontiers in Neurology, 2020)
Despite effective antiretroviral therapy (ART), mild forms of HIV-associated neurocognitive disorders (HAND) continue to afflict approximately half of all people living with HIV (PLWH). As PLWH age, HIV-associated inflammation perturbs the balance between brain matrix metalloproteinases (MMPs) and their tissue inhibitors of metalloproteinases (TIMPs), likely contributing to neuropathogenesis. The MMP/TIMP balance is associated with cognition, learning, and memory, with TIMPs eliciting neuroprotective effects. Dysregulation of the MMP/TIMP balance was evident in the brains of PLWH where levels of TIMP-1, the inducible family member, were significantly lower than non-infected controls, and MMPs were elevated. Here, we evaluated the MMP/TIMP levels in the doxycycline (DOX)-induced glial fibrillary acidic protein promoter-driven HIV-1 transactivator of transcription (Tat) transgenic mouse model. The HIV-1 protein Tat is constitutively expressed by most infected cells, even during ART suppression of viral replication. Many studies have demonstrated indirect and direct mechanisms of short-term Tat-associated neurodegeneration, including gliosis, blood-brain barrier disruption, elevated inflammatory mediators and neurotoxicity. However, the effect of acute versus prolonged exposure on Tat-induced dysregulation remains to be seen. This is especially relevant for TIMP-1 as expression was previously shown to be differentially regulated in human astrocytes during acute versus chronic inflammation. In this context, acute Tat expression was induced with DOX intraperitoneal injections over three weeks, while DOX-containing diet was used to achieve long-term Tat expression over six months. First, a series of behavior tests evaluating arousal, ambulation, anxiety, and cognition was performed to examine impairments analogous to those observed in HAND. Next, gene expression of components of the MMP/TIMP axis and known HAND-relevant inflammatory mediators were assessed. Altered anxiety-like, motor and/or cognitive behaviors were observed in Tat-induced (iTat) mice. Gene expression of MMPs and TIMPs was altered depending on the duration of Tat expression, which was independent of the HIV-associated neuroinflammation typically implicated in MMP/TIMP regulation. Collectively, we infer that HIV-1 Tat-mediated dysregulation of MMP/TIMP axis and behavioral changes are dependent on duration of exposure. Further, prolonged Tat expression demonstrates a phenotype comparable to asymptomatic to mild HAND manifestation in patients.